EFFECT OF COGKLAK GAME METHOD TO STUDENT’S MATHEMATICS LEARNING OUTCOME AT STATE ELEMENTARY SCHOOL - Siti Fatimah; Idawati Idawati; Mardiah Astuti; Indri Mahmudah; Masnun Baiti (Program Studi Pendidikan Guru Madrasah Ibtidaiyah, 2021)
This study aims to examine the effect of congklak game method on student learning outcomes and to determine student learning outcomes before and after the application of congklak game method in math subject. The method uses in this research is a quantitative field research. The research conducts using a true experimental design research with a one group pretest-posttest design model. The sample in this study is 15 students of class IV B. The results showed that, firstly, the results of hypothesis testing are obtained to > ttable at the significance level of 5% or 0.05 and the significance level of 1% or 0.01, namely 1.76 <37,31> 2,14 which means that there is a significant effect of congklak game method on student learning outcomes. Secondly, the average pre-test score of students is 30, and the average post-test score of students is 80. Based on these data, it can be concluded that learning using congklak game method can improve student learning outcomes in the math subject of lowest common multiple (LCM) and greatest common factor (GCF).